2014
DOI: 10.1186/1741-7015-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Managing the changing burden of cancer in Asia

Abstract: Asia accounts for 60% of the world population and half the global burden of cancer. The incidence of cancer cases is estimated to increase from 6.1 million in 2008 to 10.6 million in 2030, due to ageing and growing populations, lifestyle and socioeconomic changes. Striking variations in ethnicity, sociocultural practices, human development index, habits and dietary patterns are reflected in the burden and pattern of cancer in different regions. The existing and emerging cancer patterns and burden in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 80 publications
1
123
0
1
Order By: Relevance
“…Higher mean ages of 61.8 And 56.8 years for males and females respectively have also been reported [12]. Another study reported that cancer is commoner in elderly especially in those greater than 65 years [14]. Other non cancer related studies in the centre revealed a mean age of 46.50 years [15]; with a higher percentage of female subjects [16].…”
Section: Resultsmentioning
confidence: 83%
“…Higher mean ages of 61.8 And 56.8 years for males and females respectively have also been reported [12]. Another study reported that cancer is commoner in elderly especially in those greater than 65 years [14]. Other non cancer related studies in the centre revealed a mean age of 46.50 years [15]; with a higher percentage of female subjects [16].…”
Section: Resultsmentioning
confidence: 83%
“…Surgery is the mainstay in the treatment of patients with oral cancer. 25 In this study 74% patients reported that they received satisfactory treatment and all the patients reported that they need doctor's advice further. On the contrary, 60.6% felt they do not need regular check-up which is an important aspect of cancer treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Increase of cancer incidence and change in its age and gender [1][2][3][4][5][6] distribution during the last few decades can be attributed to better diagnostics but also to exposure to new risk factors, including xenobiotics, introduced to our living environment. Additionally, most investigations and risk assessments did not, or could not, take into account gender and age of subjects at the time of exposure to early risk factors; this knowledge gap on a critical phase of the dynamic of carcinogenesis reduces the accuracy and reliability of current assessments.…”
Section: Introductionmentioning
confidence: 99%